Ginseng berry improves hyperglycemia by downregulating hepatic gluconeogenesis and steatosis in mice with diet-induced type 2 diabetes. (August 2017) - Kim, Myung-Sunny; Kim, Soon-Hee; Park, Su-Jin; Sung, Mi Jung; Park, Jaeho; Hwang, Jin-Taek; Yang, Hye Jeong; Kim, Sunmi; Seo, Daebang; Shin, Song Seok; Hur, Haeng Jeon
Highlights: GB significantly improves obesity-induced hyperglycemia and insulin resistance. Anti-diabetic effects of ginseng berry is mediated by downregulating hepatic glucose production and hepatic steatosis. AMPK may be an important contributing regulator in the GB-mediated suppression of hepatic glucose production. Abstract: This study investigated the effect and the underlying mechanism of ginseng berry (GB) in a mouse model of type 2 diabetes, supplied with 0.05% or 0.1% dietary GB for 12 weeks. GB significantly improved hyperglycemia and insulin resistance, as demonstrated by the blood glucose and insulin levels, HOMA-IR, and GTT. Moreover, the expression of gluconeogenic genes such as PEPCK and G6Pase and the hepatic metabolites involved in the pathway of gluconeogenesis, such as glucose-6-phosphate and dihydroxyacetone phosphate, were significantly reduced by GB. Hepatic steatosis was also significantly ameliorated; TG content and expression of lipogenic enzymes and transcriptional factors such as FAS, ACC, and SREBP1 were reduced by GB. Simultaneously, AMPK phosphorylation was increased both in fatty liver and in lipid-accumulated HepG2 cells by GB. In conclusion, GB improved hyperglycemia by downregulating hepatic glucose production and hepatic steatosis, and AMPK appeared to be an important regulator of these effects.